Class, Crime, and Film Noir: Labor, the Fugitive Outsider, and the Anti-Authoritarian Tradition - Broe, Dennis (Social justice, 2003)
Part of a special issue on race, security, and social activism in the U.S. The role of the film noir genre in validating ordinary citizens who got on the wrong side of the law is explored. The success of the genre's films in gaining sympathy for their characters, the sympathetic fugitives who were protagonists against social and corporate authority, is discussed.